2014
DOI: 10.1097/inf.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Aspartate Aminotransferase-to-Platelet Ratio Index in Perinatally HIV-Infected Children in the United States

Abstract: Elevated aspartate aminotransferase-to-platelet ratio index (APRI) may signal liver fibrosis. Among 397 US children with perinatal HIV infection, APRI at baseline was > 1.5 in 0.8% (95% confidence interval [CI], 0.2–2.2%) and > 0.5 in 6.5% (95%CI, 4.3–9.4%); incidence on study was 0.5 (95%CI, 0.2–1.2) and 6.4 (95%CI, 4.8–8.3) per 100 person-years, respectively. Long-term liver outcomes after perinatal HIV infection warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Congruent with our above findings, the prevalence of evidence of at least mild to moderate fibrosis or worse (APRI > 0.5 or FIB-4 >1.45) was also consistently higher among HIV infected participants compared to their uninfected counterparts, though only statistically significant for APRI. Our prevalence rate of APRI >0.5 and >1.5 was 10% and 2%, respectively which was comparable to another domestic study of HIV-infected children whose rates were 6.5% and 0.8%[33], respectively and slightly lower compared to a Latin American study of HIV-infected children whose rate of APRI > 1.5 was 3.2%[32]. The smaller evaluable sample for FIB-4 showed a similar trend that did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Congruent with our above findings, the prevalence of evidence of at least mild to moderate fibrosis or worse (APRI > 0.5 or FIB-4 >1.45) was also consistently higher among HIV infected participants compared to their uninfected counterparts, though only statistically significant for APRI. Our prevalence rate of APRI >0.5 and >1.5 was 10% and 2%, respectively which was comparable to another domestic study of HIV-infected children whose rates were 6.5% and 0.8%[33], respectively and slightly lower compared to a Latin American study of HIV-infected children whose rate of APRI > 1.5 was 3.2%[32]. The smaller evaluable sample for FIB-4 showed a similar trend that did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have evaluated the incidence of progression of non-invasive markers of liver disease over time[29, 33] and only one was in HIV-infected children. This pediatric study only evaluated APRI and, while their rate of progression to an APRI > 0.5 was comparable to ours, that of APRI >1.5, which is suggestive of significant and advanced fibrosis, was almost 3-fold higher among our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we found 8.5% of children had an APRI >1.5 pre-cART, with an incidence of 0.77 per 1000 person-months among those with a normal baseline ALT after starting treatment. Our baseline prevalence and incidence of elevated APRI after cART were higher than the levels reported in a perinatally HIV-infected US pediatric cohort (i.e., 0.8% and 0.5 per 100 persons-years, respectively) [13]. Our median APRI (0.34, IQR 0.18–0.63) was slightly higher than that reported from an observational cohort of 1012 children with HIV at a median age 5.4 years from five Latin-American countries (0.29, range 0.05–29.67) [12].…”
Section: Discussionmentioning
confidence: 78%
“…Combination biomarkers such as the aspartate aminotransferase (AST)/ALT ratio, AST-to-platelet ratio index (APRI) and FIB4 index, have been reported as potentially useful for predicting hepatic fibrosis in children with non-alcoholic fatty liver disease [9], chronic viral hepatitis [10], chronic liver disease from various etiologies [11], as well as among perinatally HIV-infected Latin-American children [12]. A recent US study has reported low level APRI elevations prior to cART, with increasing levels over time on ART in perinatally HIV-infected children [13]. …”
Section: Introductionmentioning
confidence: 99%